Terapia Cognitiva Baseada em Mindfulness para universitários com sintomas leves e moderados de depressão, ansiedade e estresse - Alessandra de Fatima Almeida Assumpcao (2019)
High rates of depressive, anxious and stress symptoms in university students have been a concern in the world literature, mainly due to the damages resulting from the lack of adequate detection and treatment for students with these psychopathologies. Such problems have an impact on students' academic, social, family and economic life, resulting in loss of productivity, difficulties in interpersonal relationships and financial damage. It is observed the need for interventions that minimize some of these impacts and that increase the quality of life of this population. The international literature points to Mindfulness-Based Interventions (IBMs) as a promising treatment. In the Brazilian literature, however, no studies were found with the IBMs for the university population. From this scenario, the objective of this thesis was (1) to evaluate through a systematic literature review the main findings of the IBMs for university students with symptoms of depression, anxiety and stress; (2) to adapt an intervention protocol for the Brazilian reality of an IBM called Cognitive Therapy Based on Mindfulness (MBCT); (3) create a study protocol for program testing through a randomized controlled trial (RCT); (4) to evaluate the program's feasibility for the target population and (5) to evaluate the efficacy of MBCT for university students with mild and moderate symptoms of depression, anxiety and stress. To do so, in article 1 we aimed to evaluate the efficacy of IBMs for this target population through a systematic literature review. In Appendix E it is possible to verify the protocol in its entirety and the adaptations made in the MBCT to the Brazilian reality. In article 2 a study protocol was described with the methodology adopted in the RCT. In article 3 the viability of the development of the RCT was analyzed. Finally, in article 4, the RCT was carried out with university students recruited and attended at the Applied Psychology Service (SPA) at the Faculty of Philosophy and Human Sciences (FAFICH) of the Federal University of Minas Gerais (UFMG). Graduation and postgraduate students with mild and moderate symptoms of depression, anxiety, and stress, after undergoing an eligibility interview, were randomized to an experimental group (GE) and control group (CG).The EG happened for six weeks with a weekly session of 90 minutes while the GC was queued. After the six weeks of intervention, the CG received the treatment. Some measures were evaluated before the intervention, after the intervention and three months after the intervention. As a primary endpoint, the levels of depression, anxiety and stress were measured by the Beck-II Depression Inventory, the Beck Anxiety Inventory, and the Perceived Stress Scale, respectively. Self-esteem and quality of life were evaluated as secondary outcomes with the Rosenberg Self-Esteem Scale instruments and the 12-Item Health Survey. Among the results, it was observed that the MBCT intervention showed a statistically significant reduction in the symptoms of depression in the post-test, and treatment gains were maintained at the 3-month follow-up after intervention with effect sizes. Besides, the intervention also showed a statistically significant increase in the quality of life levels (MCS component) in the post-test and follow-up. Findings suggest that MBCT can help college students learn how to deal with depression symptoms, and improve quality of life.